Role conflicts in principalship its antecedents and relationships to administrative performance - Ruiz, Corazon Santos
Thirty principals, 30 assistant principals, 30 district supervisors and 300 teachers from 30 elementary schools from the National Capital Region were involved to determine the level of role conflict and the determinants and consequences of such conflicts on their administrative performance. Public school principals differed in their level of intra role and inter role conflicts. They have a moderately low level of role conflict. Personal variables (personality, maturity level, administrative experience, age, and educational qualification) and school variables (programs, ancillary services, enrolment size, faculty population) are the best predictors of role conflicts. Role conflicts are negatively related to productivity and school climate while personal maturity level and school location are positively related to productivity and school climate.